Smart cooling: Hydrogel-enhanced adaptive jet impingement utilizing through silicon via for integrated microsystems - Feng, Cheng-Yi; Aresti, Lazaros; Zhang, Peng; Wang, Da-Wei; Zhao, Wen-Sheng; Christodoulides, Paul (My University, 2025)
In three-dimensional integrated circuits, variations in power consumption across different regions lead to uneven temperature distribution, which can compromise system stability and reliability. While microchannels etched on the chip's backside are commonly used for cooling, traditional designs provide a fixed cooling capacity and are often inefficient in targeting specific hotspots. Moreover, straight microchannels spanning the entire system can result in overcooling in low-power areas and insufficient cooling in high-power regions. This study presents a novel design of an adaptive jet impingement cooling structure that combines hydrogel, jet impingement heat sink (JIHS) and through silicon via (TSV) technology. The structure features vertical channels and utilizes the thermally induced deformation of hydrogel to achieve adaptive cooling. This design allows the cooler to be strategically placed at hotspots, dynamically adjusting microfluidic injection in response to temperature fluctuations. As a result, overcooling in low-power regions and inadequate cooling in hotspots are mitigated, improving thermal uniformity. Compared to conventional jet impingement heat sinks, the proposed adaptive jet impingement heat sink improves temperature uniformity by 12.21 %, reduces thermal spreading resistance by 13 %, and increases maximum total thermal resistance by only 3.08 %. The maximum pressure drop increases by just 1.28 kPa. Therefore, with the increasingly complex integrated microsystem architecture, the adaptive impingement jet heat sink has better comprehensive heat dissipation performance than the traditional impingement jet heat sink under complex heat distribution.
Keywords: Jet impingement; Self-adaptability; Hydrogel; Through silicon via; Thermal performance